A Korean boy with 46,XX testicular disorder of sex development caused by duplication - Gyung Min Lee; Jung Min Ko; Choong Ho Shin; Sei Won Yang (Korean Society of Pediatric Endocrinology, 2014)
The 46,XX testicular disorder of sex development (DSD), also known as 46,XX male syndrome, is a rare form of DSD and clinical phenotype shows complete sex reversal from female to male. The sex-determining region Y (SRY) gene can be identified in most 46,XX testicular DSD patients; however, approximately 20% of patients with 46,XX testicular DSD are SRY-negative. The SRY-box 9 (SOX9) gene has several important functions during testis development and differentiation in males, and overexpression of SOX9 leads to the male development of 46,XX gonads in the absence of SRY. In addition, SOX9 duplication has been found to be a rare cause of 46,XX testicular DSD in humans. Here, we report a 4.2-year-old SRY-negative 46,XX boy with complete sex reversal caused by SOX9 duplication for the first time in Korea. He showed normal external and internal male genitalia except for small testes. Fluorescence in situ hybridization and polymerase chain reaction (PCR) analyses failed to detect the presence of SRY, and SOX9 intragenic mutation was not identified by direct sequencing analysis. Therefore, we performed real-time PCR analyses with specific primer pairs, and duplication of the SOX9 gene was revealed. Although SRY-negative 46,XX testicular DSD is a rare condition, an effort to make an accurate diagnosis is important for the provision of proper genetic counseling and for guiding patients in their long-term management.